The Role of Social Studies Teachers is to Develop Self-Efficacy in Students Who Experience Learning Difficulties in Social Studies Subjects. - Farida , Niknik; Tetep; Dahlena, Alni (SAHUR Journal, 2023)
The role of the teacher, especially in this case, the social studies teacher, is required to be able to organize classes in accordance with the expectations and demands of society. Teachers must be able to analyze the various dynamics that occur in the classroom. One of the activities carried out by the teacher is to carry out the process of growing self-efficacy in students, especially for students who experience learning difficulties. The research approach uses quantitative research methods, such as the quasi-experimental design, and the research design uses a nonequivalent control group design. Then the purposeful or judgmental sampling technique. Research data collection techniques using tests identified through pretests and posttests and non-tests through observation, interviews, and documentation studies Data validation analysis techniques use validity tests, normality tests, homogeneity tests, hypothesis tests, and normalized gain tests. The results of the study show that based on the results of data analysis and statistical calculations using Microsoft Excel 2019, there is no significant difference in pre-test results between the experimental class and the control class before learning begins. Based on the results of the data analysis after the teacher played a role in overcoming students' learning difficulties in social studies subjects, there was a significant difference between the experimental class and the control class after learning took place. In this way, social studies teachers play a role in supporting students' self-efficacy.